A Study to Assess Respectful Maternity Care (RMC) And Child Birth Experience (CBE) Among Postnatal Mothers in a Selected Hospital of District Solan, Himachal Pradesh - Kumari, Santosh; Verma, Kavita; Yachna; Kaur, Taranjeet; Dinker, Urvashi; Tanvi; Tanya; Usha; Yukta; Bisht, Swati; Kaur, Jasbir (National Journal of Community Medicine, 2025)
Introduction: In order to ensure a good Child Birth Experience (CBE), Respectful Maternity Care (RMC) entails giving birth care that is free from abuse and damage while maintaining a woman's autonomy, privacy, and dignity. Material & methods: A quantitative - non experimental research approach and descriptive research design was adopted. Total 194 Postnatal Mothers were selected by using Convenient Sampling. Data collection employed by self-structured interviews including socio-demographic, obstetrical variables, Five - Point Likert Scale on RMC, and Three - Point Likert Scale on CBE. Results: Results revealed that the majority of postnatal mothers 59.8% were highly satisfied with RMC, followed by 38.1% who were moderately satisfied, and only 2.1% who were less satisfied. Additionally, 83% of mothers reported a very good CBE, 14.9% reported a good experience, and 2.1% had an average experience. A significant positive correlation was observed between RMC and CBE scores r = 0.488, p <0.001. The mean RMC score was 59.54 ± 8.79, while the mean CBE score was 50.77 ± 6.03. Conclusion: The results underscore the vital role of in enhancing childbirth experiences. They highlight the need for targeted strategies to improve maternity services during childbirth.